Development of Pancasila Tourism Village Based on Local Potential of Jrahi Village - Muhammad Jodi Prasetiyo; Dany Miftah M. Nur; Abdul Karim (JURNAL PENDIDIKAN IPS, 2024)
Jrahi Village has enormous potential to be developed into an advanced rural tourism destination. This is because the village has interesting natural characteristics and unique socio-cultural life. The amount of potential that exists must be encouraged and developed in accordance with the socio-cultural characteristics of the local community. The purpose of this study is to analyse the local potential of Jrahi village and the efforts to develop a sustainable tourism village. This research is a field research using a qualitative descriptive approach. For data collection, researchers used interview, observation and documentation techniques. The results of this research show that there are various local potentials developed by this tourism village ranging from natural, cultural, religious, craft and culinary tourism. Embung mini jrahi is a superior tourist attraction that attracts tourists both locally and outside the region. The implications of the development of the Pancasila Jrahi Tourism village are able to contribute to increasing the income of local communities involved in tourism activities and being able to increase the village's original income. Local people who initially worked in the agricultural sector are now slowly plunging into the tourism sector. On the other hand, the sustainability of tourism villages is important in the midst of existing challenges, so that the main aspects of tourism village development referring to attractions, accessibility and amenity must be pursued optimally.